Application of switching traction and braking systems in longitudinal control for series–parallel hybrid electric buses. (1st January 2011) - Shu, Jie; Chen, Li; Yao, Jian; Yin, Chengliang
In this paper, a fuzzy adaptive control law for switching traction and braking systems to stop a hybrid electric bus is proposed. Moreover, the fuzzy adaptive controller takes the actuator constraints into account. Also, online estimation of external disturbance has been used in the design of control law for the robustness of the controller. The stability and convergence properties of the longitudinal brake controller are analytically proved by using Lyapunov stability theory and Barbalat's lemma. The proposed algorithm is examined for platoon performance. The results of numerical simulation and processor-in-loop simulation demonstrate the control stability of trajectory tracking.